Badanie efektywności dydaktycznej szkoleń bibliotecznych dla studentów w Bibliotece Uniwersytetu Łódzkiego w latach 1954-2010 - Jerzyk-Wojtecka, Justyna; Felińska, Renata (Acta Universitatis Lodziensis. Folia Librorum, 2010)
The authors try to show the system of library courses for students in the Library of the University of Łódź. Since 1954 courses of library education have been arranged each academic year. The formula of those courses has changed few times. After the enlargement of the Library building and updating the circulation of collections, a new model of the courses has started. Article presents the historical view of the library education for students, the new formula of the courses and the results of a survey. In the survey students were asked what they think about the library education and the abilities they acquired during the course. Student’s answers could have influence the shape of the future courses.